Fabrication of frequency selective structure and evaluation of microwave transmission on energy saving glass - Lim, Huey Sia (2015)
The use of energy saving glass has become very popular in the modern day building design. This energy saving property is achieved by applying a very thin tin oxide (SnO2) coating on one side of the glass. This coating can provide good thermal insulation to the buildings by blocking infrared rays while being transparent to visible part of the spectrum. Drawbacks of these energy saving windows is that it also attenuates the transmission of useful microwave signals through them. These signals fall within the frequency band of 0.8GHz to 2.2GHz. In order to pass these signals through the coated glass, the use of aperture type frequency selective surface (FSS) has being proposed. In the present work, SnO2 thin film with FSS structure was fabricated using RF magnetron sputtering technique and printed circuit board technology. Deposition time, dissipation power and oxygen flow rate were varied during the sputtering deposition process. Atomic force microscopy (AFM) and field emission-scanning electron microscopy (FE-SEM) were used to analyze the surface morphology and roughness of the SnO2 thin film. Two point electrical probe analysis was used to determine the sheet resistance and resistivity of the SnO2 thin film. Thickness of SnO2 thin film was measured using surface profiler. Good correlation between the surface properties and electrical properties of SnO2 thin film was obtained. Microwave transmission through SnO2 coated glass with FSS structure was also analyzed using network analyzer. The result of computer simulation was confirmed and consistent with the network analyzer results that showed the improvement of SnO2 coated glass with the FSS structure. Thermal analysis demonstrated that FSS structure had allows the transmission of GSM mobile signal penetrate in the buildings while blocking the infrared light with the SnO2 film properties.